Development of an organizational culture of continuous improvement process across CGIAR breeding programs to support operational excellence - CGIAR Excellence in Breeding Platform (2020)
To meet funders/end-users needs, CGIAR breeding programs are modernizing their breeding operations. This doesn't mean a change here/there, but a culture of continuous improvement. By adopting LEAN methodologies (LM) IRRI has been engaging the operational team supporting the modernization process. LM were established to support operational teams defining their processes adding value to clients' needs. Adopting LM allows breeding teams to better structure processes, reducing redundancies/errors, eliminating waste and bringing effective delivery needs emphasising teamwork within the process.